Health Reform and the Medicaid Expansion: Planning for Tennessee’s Fiscal Future - Allison Thigpen (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
In March 2010, Congress approved large changes for the health care industry, including an expansion of the existing Medicaid program. This paper explores the potential fiscal impacts of this Medicaid expansion for the state of Tennessee. First, the development of Medicaid and TennCare, the current recession, and the broader health reform law are outlined to contextualize the Medicaid expansion. Second, the population to be covered by the expansion is characterized to understand cost implication and reveal strategies for cost containment and health improvement. Next, the costs of the program are estimated under set assumptions and the strength of the impact of two main variables -- inflation and enrollment -- are analyzed. Additionally, this section looks at savings the state may realize as well as some corollary consequences of the increased federal funding to the state.